MODEL PEMANTAUAN PERSEDIAAN LOGISTIK KEBENCANAAN DALAM MENGHADAPI BENCANA BANJIR TAHUNAN DI KABUPATEN ACEH TAMIANG - Nasrullah .; M. Dirhamsyah; Yusya Abubakar (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
This study aims to produce a optimal and effective effort meet the availability of disaster logistics with minimum requirements, appropriate methods of undertaking disaster logistics supplies, and a model of disaster logistics inventory monitoring. This research using approach system method which consist of input element, process element, and element of ouput supported by primary data and secondary data obtained by in-depth interview and observation. The results of this study indicate that by evaluating the rainfall data in Aceh Tamiang District the appropriate time in logistic supply is in June. The calculation of economic order quantity method with general economic logistic rice standard for each order is 282 kilogram with frequency of ordering 12 times a year and total cost of economical inventory every time Rp 208.075, meanwhile, with economical rice logistic special standard every time the order is 416 kilogram with the frequency of ordering 12 times a year and the total cost of economical inventory every time Rp 208.158. The model of disaster logistic monitoring is formulated by evaluating several components on the capacity aspect of local government and is expected to be done routinely and periodically.